Sistema fotovoltaico monocristalino para bombeamento de água - Moreira, Carlos Alberto Machado; Seraphim, Odivaldo José [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP] (EIA Energy in Agriculture, 2012)
Since ancient times, it has been a huge challenge to all people around the world to manage to get their fresh water, keeping it clean and providing it to every human being, so that it can be used for their daily needs. This is especially true for small properties in the countryside and in isolated areas with low demographic density. Pumping the water in those regions is a solution that rationalizes its use in domestic chores, in animal rearing and in the irrigation systems of cultivated areas. Making feasible local, renewable and non-polluted energetic alternatives is the aim for those areas that are usually far away from the public electric network. Using photovoltaic solar energy is the alternative now proposed. For this objective was built a system with two monocrystalline panels, one pump, two water tanks, two level sensors and a solenoid valve to pump water, using a pump powered an array of monocrystalline solar panels. The main goal was to compare their rate of water flow and their energy consumption. The use of one data acquisition equipment allowed collecting meteorological, electrical and hydraulic values, and also serving for the control and activation of the pumping system. During four months in a row as from April 2009, arrangements with one or two panels were tested. Mathematics correlations and adjustment lines were used to interpret the behavior of obtained dataset. During the analyzed period the system followed the linear equations with great accuracy. The daily average amount of water pumped by the several tested arrays stayed between 1,100 and 2,500 liters, and that is enough to supply a small rural property. The pumping system with two panels effectively showed the major amount of water, but a system with one panel can be an economical solution until 1,500 liters on day. It did not characterize a direct relationship between power or quantity of photovoltaic panels and daily outflow of water pumping.

Conseguir água própria para o consumo, preservar esta água limpa e fazer com que ela chegue até cada ser humano para que possa ser utilizada em suas necessidades diárias é um enorme desafio a todos os povos do mundo desde a antiguidade. Isto ocorre principalmente em pequenas propriedades nas áreas rurais, em regiões isoladas e com baixa densidade demográfica. O bombeamento da água, quando ela é encontrada no local, é uma solução que racionaliza seu uso nas atividades domésticas, na criação de animais e nos sistemas de irrigação de áreas cultivadas. Viabilizar alternativas energéticas locais, renováveis e não-poluentes é a meta perseguida para essas regiões que geralmente estão distantes das redes públicas de energia elétrica. Utilizar a energia solar fotovoltaica é a alternativa proposta por este trabalho. Para isto foi montado um sistema com dois painéis monocristalinos, composto por uma moto-bomba, duas caixas-d água, dois sensores de nível e uma válvula solenóide para bombear água, utilizando uma bomba energizada por arranjos de painéis solares monocristalinos. O objetivo foi comparar dados de vazão e energia elétrica consumida pelas bombas. A utilização de um equipamento de aquisição de dados permitiu coletar valores meteorológicos, elétricos e hidráulicos, servindo também para controle e acionamento do sistema. Durante quatro meses consecutivos, a partir de abril de 2009, arranjos com um ou dois painéis foram testados. Correlações matemáticas e curvas de ajustes foram usadas para interpretar os dados obtidos. No período analisado o sistema obedeceu a equações lineares com grande exatidão. O volume médio diário de água bombeada pelos arranjos testados variou entre 1.100 e 2.500 litros, suficiente para atender uma pequena propriedade rural. O sistema de bombeamento com dois painéis efetivamente apresentou volume maior de água bombeada, mas a utilização de apenas um painel pode ser uma solução econômica para um volume de água de até 1.500 litros diários.
Water pumping with photovoltaic monocrystalline system
Keywords: Water supply; Solar energy; Photovoltaic panel; Abastecimento de água; Energia solar; Painel fotovoltaico